Isolation of supressing agents of Pseudomonas solanacearum E. F. Smith in tomato (Lycopersicon esculentum). - Cartín, Jorge M.; Wang, Amy (Agronomía Mesoamericana, 2016)
Three soil samples were collected at the highlands of Cartago (Cipreses, Pacayas and Tierra Blanca) Costa Rica and were placed in individual trays. Then, 50 seeds of tomato variety Hayslip were sown in each tray. After 40 days, plants were inoculated with a Pseudomonas solanacearum. Two weeks after the inoculation, healthy and diseased plants were incorporated and left to decompose for 12 days, in order to allow establishment of the bacteria in the soil. Then, 70 seeds were sown in each tray. After 42 days, plants were inoculated by inundation with a suspension of 103 CFU/ml of P. solanacearum. Surviving plants were taken to the laboratory and desinfected; cuts were made at the base of the stems, then the epidermis was removed and cuts were placed in test tubes containing sterile water for 90 minutes. The Petri dishes were then incubated for 48 hours at 28°C. From the growing bacteria, antagonism on P. solanacearum was evaluated by scratching Pctri dishes with each bacteria over same medium alrealy dcseribcd. Out of 22 bacteria originally obtained, 12 showed antagonism on P. solanacearum. Antibiotic substances might be involved in this process.